The Application Of Legal Sociology Approach In Diversion Policy And The Role Of The Community Based On Law No. 11 Of 2012 Concerning The Juvenile Criminal Justice System (SPPA Law) - Hendra Busriani (ISNU Sumatera Utara, 2024)
This study discusses the application of the legal sociology approach in diversion policy and the role of the community based on Law No. 11 of 2012 concerning the Juvenile Criminal Justice System (SPPA Law), as well as the challenges in its implementation. The SPPA Law is designed as a legal umbrella to handle children's cases with an approach oriented towards rehabilitation and restorative justice, rather than mere punishment. The diversion policy regulated in Article 7 of the SPPA Law aims to resolve juvenile criminal cases outside the court through a deliberation mechanism, involving the victim, the perpetrator, the family, and the community. Community participation is key in the process of reintegrating children into their social environment, thereby reducing the impact of negative stigma and encouraging holistic child recovery. However, the implementation of this policy still faces various challenges, such as the lack of understanding of law enforcement officials about restorative justice, the limited number of special child coaching facilities, and the community's attitude that is often still repressive towards children who commit criminal acts. This study uses a sociological juridical approach with normative-empirical methods to examine the gap between the rules in the SPPA Law and practice in the field. The results of this study are expected to provide insight into the importance of synergy between law enforcement and the community in creating an effective, humane, and rehabilitation-oriented juvenile criminal justice system, so that children who are in contact with the law can obtain adequate protection and opportunities to contribute positively to society.